Preliminary Identification of Candidate Genes Related to Survival of Gynogenetic Rainbow Trout (Oncorhynchus mykiss) Based on Comparative Transcriptome Analysis - Konrad Ocalewicz (Animals, 2020)
In the present research, the eggs from four rainbow trout females were used to provide four groups of gynogenetic doubled haploids (DHs). The quality of the eggs from different clutches was comparable, however, interclutch differences were observed in the gynogenetic variants of the experiment and the survival of DH specimens from different groups varied from 3% to 57% during embryogenesis. Transcriptome analysis of the eggs from different females exhibited inter-individual differences in the maternal genes’ expression. Eggs originating from females whose gynogenetic offspring had the highest survival showed an increased expression of 46 genes when compared to the eggs from three other females. Eggs with the highest survival of gynogenetic embryos showed an up-regulation of genes that are associated with cell survival, migration and differentiation (tyrosine-protein kinase receptor TYRO3-like gene), triglyceride metabolism (carnitine O-palmitoyltransferase 1 gene), biosynthesis of polyunsaturated fat (3-oxoacyl-acyl-carrier-protein reductase gene), early embryogenic development (protein argonaute-3 gene, leucine-rich repeat-containing protein 3-like gene), 5S RNA binding (ribosome biogenesis regulatory protein homolog) as well as senescence and aging (telomerase reverse transcriptase, TERT gene), among others. Positive correlation between the genotypic efficiency and egg transcriptome profiles indicated that at least some of the differentially expressed genes should be considered as potential candidate genes for the efficiency of gynogenesis in rainbow trout.